The Role of General Education in Developing Students’ Critical Thinking Skills - Dicki Hartanto (CENDEKIA INDONESIA, 2026)
This study aims to examine the role of general education in developing students’ critical thinking skills in secondary schools. The research employed a qualitative descriptive design to gain an in-depth understanding of how general education contributes to the development of higher-order thinking skills. The participants of this study included teachers and students selected through purposive sampling based on their involvement in general education learning. Data were collected through classroom observations, semi-structured interviews, and documentation. The data were analyzed using qualitative techniques, including data reduction, data display, and conclusion drawing. The findings reveal that general education plays a significant role in fostering students’ critical thinking skills. Instructional strategies such as discussion-based learning, problem-solving activities, collaborative learning, and effective questioning techniques were found to enhance students’ ability to analyze, evaluate, and apply knowledge. Additionally, the integration of real-life contexts and interdisciplinary learning made the learning process more meaningful and supported the development of critical thinking. However, several challenges were identified, including limited instructional time, large class sizes, and varying student abilities, which may affect the effectiveness of these strategies. In conclusion, general education has strong potential to develop students’ critical thinking skills when implemented through interactive and student-centered approaches. The study suggests that teachers should adopt diverse and innovative teaching strategies to create meaningful learning experiences and improve students’ critical thinking abilities.